Defect engineering in AlGaN-based UV optoelectronic heterostructures grown on c-Al2O3 by plasma-assisted molecular beam epitaxy. Issue 1741 (13th March 2015) - Rouvimov, Sergei; Jmerik, Valentin N.; Nechaev, Dmitrii V.; Ratnikov, Valentin V.; Toropov, Alexey A.; Shevchenko, Eugenii A.; Brunkov, Pavel N.; Rzheutski, Mikolai V.; Lutsenko, Eugenii V.; Ivanov, Sergey V.
ABSTRACT: AlGaN-based SQW heterostructures grown by plasma-assisted molecular beam epitaxy on c-Al2 O3 substrates have been studied with high resolution transmission electron microscopy (HR TEM), photoluminescence spectroscopy and x-ray diffraction. The high-temperature (780°C) synthesis of the AlN buffer layer nucleated on c-Al2 O3 by a migration enhanced epitaxy and including several ultra-thin GaN interlayers grown under moderate N-rich conditions was shown to be the optimum approach for lowering the threading dislocations density down to 10 8 -10 9 cm -2 . HR TEM study has confirmed the fine structure of single quantum wells (SQW) formed by a sub-monolayer digital alloying technique and revealed different kinds of compositional inhomogeneities in the Alx Ga1-x N barrier layers of the heterostructures, including the formation of Al-rich barriers induced by the temperature-modulated epitaxy and the spontaneous compositional disordering along the growth axis for x=0.6-0.7. The influence of these phenomena on the parameters of the mid-UV stimulated emission observed in the SQW structures has been studied as well.